Pengendalian Inflasi melalui Kebijakan Moneter Syariah: Zakat, Wakaf, dan Larangan Riba (Sharia Monetary Policy for Inflation Control) - Lili Almaida; Lollita Larassati; Rahma Nadia; Melisa Nuraini; M Bambang; Menzen Menzen; Andang Sunarto (As-Syirkah: Islamic Economic & Financial Journal, 2026)
Inflation is an economic challenge that has a major impact on macroeconomic stability and public welfare. This study aims to analyze the development of inflation in Indonesia in the period 2023 to April 2025, identify the types of inflation that occur, and explore alternative solutions to control inflation from an Islamic economic perspective. The method used is library research with a qualitative approach, where data is collected from secondary sources such as official reports, conventional and Islamic economic literature, and previous research results. The results of the study show that inflation in Indonesia during this period was relatively low and under control, with a dominant tendency in the form of cost-push inflation and seasonal inflation. In Islamic economics, inflation is viewed not only as an economic phenomenon, but also as a result of moral decay and inequality in distribution. Therefore, the solutions offered include the prohibition of usury, the implementation of zakat, infaq, and waqf, and a justice-based fiscal policy. This study recommends the integration of Islamic economic principles in national inflation control policies in order to create sustainable and socially just price stability.